Strategi Caleg Perempuan Terpilih Sebagai Anggota DPRD Kabupaten/Kota Di Kalimantan Selatan Pemilu 2014 - Fatrawati Kumari, Ridhahani Fidzi, Wardah Hayati, (Muadalah, 2015)
Womenâs right in politics has been regulated by law. Specifically, Law No. 12 of 2003, articleÂ 65, paragraph 1, has specified the quota of women in the general election by 30 percent.Â Nevertheless, the womenâs representation in the legislative has not met expectations. TheÂ data from the Ministry of Women Empowerment and Child Protection has shown thatÂ the number of women who sit in the House of Representatives (DPR) is only 18 percent,Â while in the Peopleâs Consultative Assembly (MPR) and the Regional Representative Council(DPD) are respectively 20 and 27 percent,. The data also shows that the women who sit inÂ the Province Legislative Council (DPRD Provinsi) is only 16 percent, and 12 percent in theÂ City Council (DPRD Kota) dan the Regency (DPRD Kabupaten). The success of the womenÂ candidates to become the members of legislature can not be separated from their sincerityÂ and persistence efforts to apply the right strategy. Strategies determine the success ofÂ the candidates. Referring to the importance of strategy, thus, it becomes significant tospecifically examine the candidatesâ strategies in a study entitled: âStrategi Caleg PerempuanÂ Terpilih sebagai Anggota DPRD Kabupaten/Kota di Kalimantan Selatan Pemilu 2014âÂ The problem formulated in this study is how the strategies implemented by theÂ elected women candidates as the members of the City Council and the RegencyÂ in South Kalimantan in the 2014 Election. The study employs qualitative methodÂ through descriptive study. The study takes place in South Kalimantan whereÂ the Â samples are taken from seven locations with a diverse number of votes.Â There are three findings from the study. First, in general, the elected women candidatesÂ have employed the strategy of political marketing and the strategy of social capital. TheÂ strategy of political marketing employed by the elected candidates include: segmentationÂ and mapping, campaign and positioning, and evaluation and monitoring. Second, thesocialization is held privately by door-to-door visiting the people. The candidates carry outÂ periodic evaluation and monitoring with involving their successful team. Third, the entireÂ candidate has a good social capital, i.e. the ability to relate and cooperate with others.Â The social capital includes: the ability to build network and to gain thrust, and to bindÂ themselves to the religious beliefs of the candidates and the public in their electoral districtÂ